Brain Functional Networks Study of Subacute Stroke Patients With Upper Limb Dysfunction After Comprehensive Rehabilitation Including BCI Training - Wu, Qiong; Yue, Zan; Ge, Yunxiang; Ma, Di; Yin, Hang; Zhao, Hongliang; Liu, Gang; Wang, Jing; Dou, Weibei; Pan, Yu (Frontiers in Neurology, 2020)
Brain computer interface (BCI) based training had shown promising in treating patients who have suffered from stroke with upper limb (UL) paralysis. However, in the real world study, most stroke patients received comprehensive treatment, not only includes BCI but also routine training. The purpose of this study was to investigate the topological alterations in brain functional networks following the comprehensive treatment including BCI training in subacute stage of stroke. Twenty-five hospitalized subacute stroke patients with moderate to severe UL paralysis were assigned into 2 groups: 4-week comprehensive treatment, including routine and BCI training (BCI group, n = 14) and 4-week routine training without BCI support (control group; n = 11). Functional assessments of upper limbs were performed before and after training, including Fugl-Meyer Assessment-UL (FMA-UL), Action Research Arm Test (ARAT), and Wolf Motor Function Test (WMFT). Neuroimaging assessment of functional connectivity (FC) in BCI group was performed by rest state functional MRI. After training, compared with baseline, all clinical assessments improved significantly in both group, FMA-UL(P ＜ 0.05), ARAT(P ＜ 0.05) and WMFT(P ＜ 0.05). Meanwhile, better functional improvements were observed in BCI group, FMA-UL(P ＜ 0.05), ARAT(P ＜ 0.05) and WMFT(P ＜ 0.05). Meanwhile, FC of BCI group increased across the whole brain, including temporal, parietal, and occipital lobe and subcortical regions. More importantly, increased inter-hemispheric FC between somatosensory association cortex and putamen was strongly positively associated with UL motor function after training. Our findings demonstrate that comprehensive rehabilitation including BCI training can enhance the UL motor function better than routine training for subacute stroke patients. The reorganization of brain functional networks topology in subacute stroke patients, allowing increased coordination between multi-sensory and motor related cortex and the extrapyramidal system. Future long-term, longitudinal, controlled neuroimaging studies are needed to identify the effectiveness of BCI training and approach to promote brain plasticity on subacute stage of stroke.